Pengaruh Kualitas Pelayanan Terhadap Niat Ulang Dengan Menggunakan Produk Yang Lain Melalui Kepercayaan Nasabah Bank Syariah Mandiri Kantor Cabang Boulevard di Surabaya - Aditya Okta Viandhy; Ririn Tri Ratnasari (Universitas Airlangga, 2014)
This study aims to determine the effect of service quality on intention to re-use products other Bank Syariah Mandiri through the trust as an intervening variable.The method used is quantitative approach. Characteristics of the sample used is 30 customers of Bank Syariah Mandiri Boulevard branch in Surabaya who use a particular product. Sampling is using nonprobability sampling with purposive sampling procedure. The analytic technique is used path analysis or path analysis.The results showed that the quality of services significantly influence customer confidence in Bank Syariah Mandiri Boulevard in Surabaya. Other results show that trust significantly influence purchase intention by re-using the products of Bank Syariah Mandiri others. While service quality does not significantly influence customers' purchase intention by re-using the products of Bank Syariah Mandiri others.Advice for Bank Syariah Mandiri branch in Surabaya Boulevard to always improve the quality of service to customers through good SERVQUAL and maintain the trust that exists between the customer and the bank to always be honest and maintain the trust that has been given by the customer to the bank. For further research can add variable customer loyalty in the Islamic perspective. REFERENCESAjzen, I. 1991. The Theory of Planned Behavior. Organizational Behavior and Human Decision Processes. Nomor 50. Hlm. 179-211. Diunduh dari http://people.umass.edu/psyc661/ pdf/tpb.obhdp.pdf pada November 2011.Anshori, Muslich dan Sri Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press.Arvan Pradiansyah, (1999), “ Peranan Kepemimpinan dalam Membangun Kepercayaan di Tempat Kerja ”, Usahawan , No. 19 th. XXVIII September, hal. 23 – 25.Azwar, Saiffudin. 1997. Sikap Manusia Teori dan Pengukurannya. Yogyakarta: Pustaka Belajar.Chamhuri, N dan PJ. Batt. 2009. Factor Influencing Consumer’s Choice of Retail Stores for Fresh Meat in Malaysia. (Online) diakses pada 1 Mei 2012.Cronin, J. Joseph JR dan Steven A. Taylor. 1992. “Measuring Service Quality: A Reexamination and Extention. Journal of Marketing. Vol. 56. July, p. 55-68.Dunn, Elizabeth. W., Huntsinger, Jeffrey., Lun, Janetta., & Sinclair, Stacey.. 2008. The gift of similarity: Howgood and Bad Gifts Influence Relationships. Social Cognition. Volume 26: 469-481.Eriksson, Kent and Lofmarck Vaghult. 2000. Effects on New Customer Acquisition by Retained Customers in Professional Services, 16th IMP Conference, Bath.Ferdinand, Augusty T.2002. Kualitas Strategi Pemasaran: Sebuah Studi Pendahuluan. Jurnal Sains Pemasaran Indonesia. Vol 1, No.1. hlm. 107-119.—————-. 2006. Structural Equation Modelling dalam Penelitian Manajemen. Edisi pertama. Semarang: Universitas Diponegoro.Ghozali,I. 2006. Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit- UNDIP.Hermansyah. 2008. Hukum Perbankan Nasional Indonesia. Jakarta: Prenada Media Group.Hellier, Philip K, Gus M.Geursen, Rodney A.Carr, John A.Rickard. 2003. Costumer repurchase intention: A general structural equation model. European Journal of Marketing. Vol. 37. Issue 11.Indriantoro, Nur dan Bambang Supomo. 2002. Metodologi Penelitian Bisnis untuk Akuntansi dan Manejemen. Edisi Pertama. Yogyakarta:BPFE. Infobank. 2007. Vol XXIX no. 344.Karim, Adiwarman A. 2004. Bank Islam. Jakarta: PT Rajagrafindo Persada.Kotler, Philip dan Gary Amstrong. 2001. Prinsip-prinsip pemasaran. Edisi Kedelapan. Jakarta: Penerbit Erlangga.——– dan Kevin L.Keller. 2003. Manajemen Pemasaran. Edisi Kedua. Jakarta: Indeks.Ling, Leong Quee, M.Shahrim AK.H, Mohhidin Othman, Noranizan M Adzahan, Sridar Ramachandran. 2010. Relationship Between Malaysian Food Image, Tourist Satisfaction, and Behavioural Intention. World Applied Sciences Journal 10 (Special Issue of Tourism and Hospitality) 164-177.Lupiyoadi, Rambat dan A. Hamdani. 2008. Manajemen Pemasaran Jasa. Jakarta: Salemba Empat.Maholtra, Naresh K., 1999. Marketing Research : An Applied Orientation, 3rd edition, Prentice Hall, Inc., New Jesrey.Maholtra, Naresh K., and Avinandan Mukherjee, 2003. Analysing the Commitment Service Quality Relationship: A Comparative Study of Retail Banking Call Centres and Branches, Journal of Marketing Management, 2003, 19, 941-971.Moorman, Christin, Gerald Zaltman and Rohit Deshpande (1993) Factors Affecting Trust in Market Research Relationship, Journal Marketing Research, Vol. 57 (January), 81-101.Morgan, Robert M., dan Shelby D. Hunt. 1994. The Commitment Trust Theory of Relationship Marketing. Journal of Marketing. Volume 58: 20-38.Nazir, Mohammad. 2003. Metode Penelitian. Jakarta: Ghalia Indonesia.Othman, Abdulqawi and Owen Lynn. 2001. The Multi Dimensionality of CARTER Model to Measure Customer Service Quality in Islamic Banking Industry: A Study in Kuwait Finance House. International Journal of Islamic Services. Volume 3: 1-12.Sari, Dhanty V.P. 2012. Pengaruh Perilaku islami Pemasar terhadap Kepercayaan dan Istiqomah yang dimoderasi oleh Tingkat pengetahuan Agama nasabah pada BRI Syariah di Surabaya.Skripsi Diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Sarwono, Jonathan. 2006. Analisis Data Penelitian Menggunakan SPSS. Jakarta: C.V. Andi Offset.Schiffman, Leon G. And Leslie Lazar Kanuk. 2000. Consumer Behaviour. Seventh Edition. Upper SaddleRiver. New Jersey: PrenticeHall Inc.Simamora, Bilson. 2003. Memenangkan Pasar Dengan Pemasaran Efektif Dan Profitabel. Jakarta : PT. Gramedia Pustaka Utama.Sirdeshmukh, Deepak, Jagdip Singh, and Barry Sabol. 2002. Consumer Trust, Value, and Loyalty in Relational Exchanges, Journal of Marketing. Volume 66: 15-37.Tasmara, Toto. 2001. Kecerdasan Ruhaniah. Jakarta: GemaInsani Press. Wibisono, Darmawan. 2000. Riset Bisnis. Bandung : Ganesha Exact.Zeithaml, Valarie.A. and Bitner, Mary. Jo. 2000. Services Marketing: Integrating Customer Focus Across the Firm: 2nd Edition. London: Irwin McGraw Hill.